TAM (Technology Acceptance Model) Approach to Analyze Community's Interest in Using E-money - Rinwantin; Yanti Pujiastuti (Journal of Applied Sciences in Accounting, Finance, and Tax, 2022)
TAM (Technology Acceptance Model) is a model that can be used to see the extent to which a technology can be well accepted by the community. Cashless payment is a product that can support the creation of a cashless society in accordance with Bank Indonesia policies. This research was conducted with the aim of providing an overview of the interest in using e-money using TAM. The sample in this study amounted to 100 respondents, the collected data were analyzed using linear regression with the conclusion that the significance was less than 0.05 for the perceived benefit factor (ρ value = 0.000) and ease of use (ρ value = 0.023). The conclusion is that the perceived benefits and ease of use have a positive and significant effect on the interest in using cashless payment